Evaluation of Anti-Inflammatory Activity of Pseudananas macrodontes (Morr.) Harms (Bromeliaceae) Fruit Extract in Rats - Errasti, María Eugenia (2013)
Several species of the family Bromeliaceae are characterized by the production of proteases in unusual amounts, especially in fruits. Bromelain, an extract rich in cysteine endo-peptidases obtained from Ananas comosus L., and a few other proteases have been used as anti-infl ammatory agents for some years, but bromelain is still mainly being used as alternative and/or complementary therapy to the treatment with glucocorticoids, nonsteroi-dal antirheumatics, and immunomodulators. In this study, the anti-infl ammatory action of a partially purifi ed extract from Pseudananas macrodontes (Morr.) Harms fruits (PPEPm) is presented, whose main components are cysteine endopeptidases. The effect of PPEPm was assessed in carrageenan-induced and serotonin-induced rat paw edema, as well as in the cotton pellet granuloma model. Doses with equal proteolytic activity of PPEPm and bromelain produced signifi cantly similar anti-infl ammatory responses in the acute infl ammatory models assayed, supporting the hypothesis that proteolytic activity could be responsible for the anti-infl ammatory action. On the contrary, comparable anti-infl ammatory effects of PPEPm and bromelain in the chronic infl ammatory assay required a much lower proteolytic activity content of PPEPm, which could be due to a differential affi nity for the protein target involved in this process.